Legal concepts for nurses - Shahnaz Booraki (Journal of Holistic Nursing and Midwifery)
Nursing is an activity based on skilled, emotional, ethical and lawful practice and any minor negligence bad or unknowledgeable practice may cause the patient and nurse physical and lawful problems. The best way to prevent problems is that nurses be aware of professional standards of care and related rules. In attention to the importance of knowing the concepts of law, it is suggested that such course to be included in nursing curriculum and also for employed clinical nurses.